The Effect of Different Soil Types on Growth and Nodulation of Vigna radiata (L) Wilczek Inoculated with Vesicular-arbuscular Mycorrhiza (VAM) - Chulan, Azizah; Kamal, A.J.M; Omar, M. (1984)
The potential of using a 'natural' soil with high mycorrhizal spore count as a source of inoculum was evaluated in this preliminary experiment using 4 soil types .. Serdang, Munchong, Malacca and Bungor. Results obtained on the dry weight and P content ofplant tops was not significant between treatments but was significant between the soil types used. This could be due to the duration of the experiment being too short to enable these endogonaceous species to establish well in these soils and bring about significant growth response of the mungbean plants.